Planning in postmodern times - Allmendinger, Philip, 1968- (RTPI library series., 2001)
"Postmodern social theory has provided significant insights into our understanding of society and its components. Key thinkers including Foucault, Baudrillard and Lyotard have challenged existing ideas about power and rationality in society. This book analyses planning from a postmodern perspective and explores alternative conceptions based on a combination of postmodern thinking and other fields of social theory. In doing so, it exposes some of the limits of postmodern social theory while providing an alternative conception of planning in the twenty-first century. This title will appeal to anyone interested in how we think and act in relation to cities, urban planning and governance."--Provided by publisher